Sense and suitability : a novel - Basham, Pepper (Thomas Nelson, 2025)
"In this clean Regency rom-com, a woman with a scandalous past (and an even more scandalous secret) swears off love--until the man who broke her heart needs her help. What could possibly go wrong? Perfect for fans of Tessa Dare and Eloisa James looking for a low-spice, witty Regency romance"-- Provided by publisher.